GROUNDWATER RESOURCE ESTIMATION USING VERTICAL ELECTRICAL SOUNDING AND RESISTIVITY TOMOGRAPHY IN WEST MANOKWARI, WEST PAPUA, INDONESIA - Kammarudin, Kammarudin; Wahyudi, Wahyudi; Lewerissa, Richard; Afkril, Baina; Erari, Ishak (Universitas Mataram, 2024)
West Manokwari district in Manokwari Regency, West Papua province, Indonesia, is an area that continues to develop as part of the provincial capital region. Geologically, this area is located in three main formations: the Manokwari Formation, the Befoor Formation, and the Alluvium-littoral Formation at a depth radius between 0 and 500 meters. These formations comprise permeable sedimentary rocks that allow aquifer layers to develop. This study employed the geoelectric resistivity method, using both the Wenner and Schlumberger configurations, to identify the potential of groundwater in the West Manokwari district and address the scarcity of clean water sources for the local community. Subsurface interpretation was conducted on three measurement lines using forward modeling and inversion techniques, such as earth resistivity tomography and vertical electric sounding. The results of this interpretation indicate that the subsurface rock resistivity for the three lines is generally consistent and supports each other. The subsurface can be divided into four main layers: topsoil, limestone, sandstone, and bedrock. At the surface, rock resistivity is dominated by high values up to a depth of 6 m, after which it decreases to a depth of 30 m, which is considered a potential aquifer layer for exploration with medium to low resistivity. A bedrock layer with a resistivity of over 2000 Î©m is estimated to be at depths greater than 30 m. This study is expected to serve as a valuable resource for groundwater exploration in the West Manokwari district of West Papua Province.